Social sustainability labels: Promises and reality in the example of Fairtrade-coffee - Pio Baake; Jana Friedrichsen; Helene Naegele (DIW Weekly Report, 2018)
Fairtrade certification is intended to improve both the income and living conditions of producers, thereby creating more fairness in international trade. However, theoretical considerations and empirical studies show that this goal is only achieved to a limited extent, at least for coffee: Faitrade certification leads at best to small increases in income for coffee farmers. The results on the reduction of income volatility, payments used to implement social projects, and improved access to credit are also mixed. Fairtrade is a means of market segmentation for roasters and retailers.
Keywords: F14; F63; L30; O13; 330; coffee; consumers; Fair Trade; livelihood